EFEKTIVITAS KEBIJAKAN BALI NDESO MBANGUN DESO DI KABUPATEN PEKALONGAN (Studi Kasus Pelaksanaan Bantuan Keuangan Pemerintah Provinsi Jawa Tengah Kepada Pemerintah Desa Tahun 2009 -2012 dalam Bidang Pertanian Di Desa Sawangan, Desa Babalan Kidul dan Desa Be - Budi Nur Hadi Wibowo; Kushandajani .; Dzunuwanus Ghulamanar (Journal of Politic and Government Studies, 2015)
This research was undertaken with the policy background Bali Ndeso Mbangun Deso the government of the province of central java. in Efforts to Realize economic development to the optimal -based society in the villages, then plays in Achieving financial assistance to the government developing village years 2009-2012 to 1776 village .The number of funds provided by provincial budget amounting to Rp 100,000,000,- (one hundred million rupiah) for the village call now. Financial aid funds this is a stimulus, just where is dedicated to increasing economic-based society (agriculture, animal husbandry, fisheries, Small and medium enterprises), as well as its use through a system of revolving. This study focused on the implementation of the in the fields of agriculture.Researchers used a method of the qualitative study that refers to the type of descriptive research on the subject of study is analytical. The parties that is concerned and is Involved in the implementation of a policy of financial assistance to the village administration of them developing years 2009-2012 provincial central java Bapermades BPMPKB pekalongan district, the village administration Sawangan, village babalan kidul, bebel village and the community. Data collection techniques through observation, interviews, documentation, the literature study and then Analyzed through a data reduction technique, presentation of the data and verification / draw any Conclusions. The result of this research Showed that the implementation of financial assistance to the village administration developing years 2009-2012 in the fields of agriculture has not produces Increased agricultural productivity Effectively, it is the absence of technical guidance about the business development of agriculture. Besides, to distribute the loans prone to congestion if the result of the harvest is not optimal, Thus reducing the Attainment of participatory by the society. To fix this policy, of course, the need for improvement both administratively and technically. A grant plus, intensivity coaching of Bapermades and related local government offices agriculture to farmers, maximizing control system and irrigation infrastructure improvements. Keywords : Effectiveness, Policy, Rural Assistance, Agriculture